The Role and Tasks of Graphic Information in the Activities of Arts, Designers and Architects - Raimkulovich, Saparov Khazratkul (European Journal of Life Safety and Stability (2660-9630), 2021)
The process of implementation and improvement of the "National Training Program" of the Republic of Uzbekistan has begun. This process requires a revision of educational standards and modernization through the use of information technology. Training of architects, art critics, design specialists consists of three logics, which are connected with the process of transition of our country to a market economy.